2015
DOI: 10.1007/s10895-015-1693-z
|View full text |Cite
|
Sign up to set email alerts
|

Cd-Cysteine Nanorods as a Fluorescence Sensor for Determination of Fe (III) in Real Samples

Abstract: A new Cd-Cysteine complex nanorods (Cd-Cys NRs) were synthesized in one step at room temperature, and its morphology, structure and spectral properties were characterized by transmission electron microscopy (TEM), elemental analysis (EA), X-Ray diffraction (XRD), solid state and normal UV-Vis, Fourier transform infrared (FTIR) and spectrofluorometry. The developed Cd-Cys NRs were used as a fluorescence sensor for detection of Fe (III) in different aqueous matrices. The selectivity and sensitivity of the fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…For cysteine systems, new peaks emerged in the XRD pattern of pH7.5_4Cys as compared to five other XRD patterns. The peaks at 8.6, 19.7, 25.0, 26.3, 33.6, and 40.0° 2θ in the XRD pattern of pH7.5_4Cys were coincident with the patterns of Cd–cysteine nanorods reported by Ghiamati and Boroujerdi . Cd–cysteine formation in the current study could be ascribed to the Cd­(II) release to the solution due to δ-MnO 2 corrosion, followed by the precipitation of Cd­(II) with redundant cysteine.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…For cysteine systems, new peaks emerged in the XRD pattern of pH7.5_4Cys as compared to five other XRD patterns. The peaks at 8.6, 19.7, 25.0, 26.3, 33.6, and 40.0° 2θ in the XRD pattern of pH7.5_4Cys were coincident with the patterns of Cd–cysteine nanorods reported by Ghiamati and Boroujerdi . Cd–cysteine formation in the current study could be ascribed to the Cd­(II) release to the solution due to δ-MnO 2 corrosion, followed by the precipitation of Cd­(II) with redundant cysteine.…”
Section: Resultssupporting
confidence: 86%
“…The peaks at 8.6, 19.7, 25.0, 26.3, 33.6, and 40.0°2θ in the XRD pattern of pH7.5_4Cys were coincident with the patterns of Cd−cysteine nanorods reported by Ghiamati and Boroujerdi. 45 Cd−cysteine formation in the current study could be ascribed to the Cd(II) release to the solution due to δ-MnO 2 corrosion, followed by the precipitation of Cd(II) with redundant cysteine. The coexistence of Cd−cysteine and δ-MnO 2 in the pH7.5_4Cys system indicated that oxidation of cysteine by δ-MnO 2 would be impeded when cysteine was complexed with Cd(II), similar to the previous study where the complexation of glutathione by Hg(II) and Ag(I) protected thiol functional groups (R−S−) from oxidation by H 2 O 2 and Cu(II).…”
Section: ■ Results and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, several studies on Fe 3+ detection have been reported in the literature. [11][12][13][14][15] Aluminum is the third most abundant element in the biosphere. Due to increasing environmental pollution, the amount of Al 3+ accumulation in living organisms is on the increase.…”
Section: Introductionmentioning
confidence: 99%
“…The Environmental Protection Agency (EPA) determined the maximum limit value for Fe 3+ in drinking water to be 5.37 μM. Therefore, several studies on Fe 3+ detection have been reported in the literature 11–15 …”
Section: Introductionmentioning
confidence: 99%